The Ibāḍī “stages of religion” re-examined: Tracing the history of the Masālik al-Dīn - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2010)
With few exceptions, scholarly presentations of the Ibāḍī “stages of religion” (masālik al-dīn) and their corresponding Imāms (i.e. imām al-ẓuhūr, imām al-difāʿ, imām al-shirā', and imām al-kitmān) propose a simplified overview of the institution that is based on post-Ibāḍī renaissance thought on the Imāmate. This paper investigates the pre-renaissance usages of the masālik al-dīn by comparing sixth/twelfth-century Arabian and North African Ibāḍī texts on the subject. It demonstrates that Eastern and Western Ibāḍīs manipulated the concepts central to the later masālik al-dīn ideal to reflect the particular needs of each respective community. While the articulations of the masālik al-dīn differed according to region, they simultaneously utilized a similar vocabulary. This convergence implies an earlier and inherited conceptual system (most likely from the earliest Basran Ibāḍī umma) that was adapted in the medieval period to fulfil the unique needs of each community.
Keywords: Imamat – Ibadisme

Muslims, scholars, soldiers: the origin and elaboration of the Ibādī imāmate traditions - Gaiser, Adam R. (Oxford University Press, 2010)
Don de l'auteur
Keywords: Imamat – Ibadisme